Persepsi Wartawan di Kota Surakarta Mengenai Urgensi Media Baru Bagi Praktik Jurnalisme Kontemporer - Sri Herwindya Wijaya; Eka Nada Shofa Alkhajar; Pawito Pawito; Hamid Arifin; Firdastin Ruthnia Yudiningrum (LPPM Universitas PGRI Adi Buana Surabaya, 2022)
The existence of new media, especially the internet and social media, has a broad impact on the life of the human civilization, including the world of the mass media industry. The internet and social media are seen as having significant urgency because their influences on contemporary journalism practices in terms of perception, agenda setting, agenda framing, reporting practices, production and news publication. This study examines the perception of journalists in Surakarta City regarding the urgency of the internet and social media for contemporary journalism practices. This research used a qualitative method in which data were collected through interviews and documentation. The results found that (1) new media as something inevitable for the world of the press; (2) new media as modern technology has a positive impact on the world of the press; (3) new media as modern technology has a negative impact on the world of the press.